Media Edutaiment Meningkatkan Sikap dan Pratik Siswa dalam Pemilihan Jajanan Sehat pada Sekolah Dasar di Karawang - Milliyantri Elvandari; Eka Andriani (Jurnal Gizi dan Kuliner, 2020)
Food snacks are potentially contaminated with lead and heavy metals due to wind on the streets and dust carrying bacteria that pollute food and other hazards derived from the food material itself if not hygienic. Increasing attitudes and healthy practices in children can be done with nutrition counseling methods. Nutrition counseling method in this study was given through edutaiment media, one of which is snakes and ladders. Snakes and ladders is one of the games that are liked by elementary school children. This study aims to determine students' knowledge, attitudes and practices regarding healthy snacks at SDN Karawang Wetan 1. This research is a quantitative study with a Pre-Experimental design with One Group Pre-test Post Test Design. The sample consisted of 40 fifth grade students obtained by purposive sampling technique. Data collection using a questionnaire and data analysis using nonparametric 2 sample test methods related to McNemar test. The results showed that the influence of the snake ladder game media could increase students' attitudes and practices about healthy snack selection, namely p value (0,000) <? (0.05). Keywords: ladder snake, attitude, practice, healthy snacks